ROLE OF TEMPE FROM WEST SUMATRA AS A SOURCE OF VITAMIN B12 AND ANTIOXIDANT CAPACITY - Rosalina, Linda; Bernward, Bisping; Sumaryati, Syukur; Asmar, Yulastri (MSJ : Majority Science Journal, 2024)
Tempe is the most popular traditional fermented food in Indonesia that has high nutritional values such as high protein content high fatty acid content, vitamin B12, excellent digestibility, and good antioxidant content sources. Tempe also has low in anti-nutrition factors such as phytic acid, oligosaccharides. The purpose of this study is to compare traditional Tempe produced from West Sumatra, Indonesia, which is comparing the yellow and black soybeans, with a focus on antioxidant capacity. Six samples of Tempe were collected in Padang and Padang Panjang, Indonesia. Microorganism isolated from tempe samples were identified and the antioxidant capacity was determined using different antioxidant capacity assays, then Vitamin B12 determination in mocrobiological assay was perfomed. The result is included the mean of antioxidant of black soybeans = 0.008333 with a standard deviation of 0.0006429 and the mean of antioxidant of yellow soybeans = 0.008767 with a standard deviation of 0.0027465. In conclusion, it can be seen that the F count for antioxidants is 8647 with a probability of 0.042. Because of the probability value is < 0.05, then H0 is rejected or the two population variances are different (heterogeneous).